Varicella-Zoster Virus Reactivation and Increased Vascular Risk in People Living with HIV: Data from a Retrospective Cohort Study - Deborah Fiordelisi; Mariacristina Poliseno; Nicolo’ De Gennaro; Eugenio Milano; Carmen Rita Santoro; Francesco Vladimiro Segala; Carlo Felice Franco; Giorgia Manco Cesari; Luisa Frallonardo; Giacomo Guido; Giuliana Metrangolo; Greta Romita; et al. (Viruses, 2023)
Background: The increased vascular risk associated with varicella–zoster virus (VZV) reactivation is extensively established in the general population. This retrospective cohort study investigates whether this observation holds for People Living with HIV (PLWH), a group already confronting heightened cardiovascular risk. Methods: Among PLWH who initiated antiretroviral therapy (ART) at our center and have been under our care for >24 months since 1st January 2005, individuals with a history of herpes zoster (HZ) were identified, and their features were compared with those of PLWH with no history of HZ. The prevalence of ischemic events (deep venous thrombosis, stroke, and acute myocardial infarction) was calculated and compared using the chi-square test. An odds ratio (O.R.) and a 95% confidence interval (C.I.) for ischemic events following HZ were evaluated through univariate and multivariate logistic regression. Results: Overall, 45/581 PLWH reported HZ. Ischemic events followed HZ significantly more often than not (13% vs. 5%, p = 0.01). Positive serology for both VZV and HZ correlated with increased ischemic risk (O.R. 4.01, 95% C.I. 1.38–11.6, p = 0.01 and O.R. 3.14, 95% C.I. 1.12–7.68, p = 0.02, respectively), though chronic heart disease demonstrated stronger predictive value in multivariate analysis(O.R. 8.68, 95% C.I. 2.49–29.50, p = 0.001). Conclusions: VZV potentially exacerbates vascular risk in PLWH, particularly in the presence of other predisposing factors. Further research is needed to confirm our data.